Assessing organizational readiness for E-bidding in construction: An e-readiness framework and policy recommendations - Kien, Tran Trung; Hien, Nguyen Thi Thu; Van, Hoang Thi Khanh; Trung, Nguyen Van (Edelweiss Applied Science and Technology, 2025)
In the context of digital transformation and the mandatory application of e-bidding under Vietnam’s 2023 Bidding Law, assessing the organizational readiness of construction enterprises has become increasingly critical. This paper proposes a theoretical framework of E-Readiness encompassing four key dimensions: technological infrastructure, human resources and training, internal processes, and organizational culture. Based on exploratory research involving six enterprises and a pilot survey with 15 bidding officers, the study utilizes qualitative thematic analysis and descriptive statistics to refine and validate a set of readiness indicators tailored to the Vietnamese construction sector. The findings reveal significant disparities in organizational readiness levels, particularly in staffing and internal procedures. Policy recommendations are proposed to support a tiered implementation strategy aligned with varying levels of E-Readiness, aiming to enhance the effectiveness and sustainability of e-bidding adoption in the industry.